PENGGUNAAN MEDIA PEMBELAJARAN BERBASIS CANVA DALAM MODEL PBL (PROBLEM BASED LEARNING) SEBAGAI PENUNJANG PEMBELAJARAN PENDIDIKAN PANCASILA MATERI SEJARAH PERUMUSAN PANCASILA DI SDN NGALIYAN 04 - Fajriatun Nazilla; Auryna Wina; Susilo Tri Widodo (STKIP Subang, 2023)
This research aims to evaluate the benefits of using Canva-based learning media in the Problem Based Learning (PBL) model as a support for learning Pancasilaeducation, focusing on material on the History of the Formulation of Pancasila at SDN Ngaliyan 04. The research method involves interviews, observation and literature review. Interviews were conducted with 4th grade elementary school teachers to identify students' problems related to the material, while observationsfocused on students' responses to the material, especially in the use of interactive teaching media. A literature review was conducted to gain contextual understanding and previous research findings. The research results showed that the application of Canva in PBL had a significant positive impact on student understanding, with the experimental group showing better improvement compared to the control group who used conventional learning. Canva provides an attractive and interactive display, presents material visually, and develops students' critical thinking and problemsolving skills. This research confirms that Canva can be an effective alternative for improving student learning outcomes and promoting creative and problem-solving skills, especially in the context of Pancasila education learning at the elementary level.